2013
DOI: 10.1073/pnas.1220703110
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 dimer–monomer interconversion during HDL generation revealed by single-molecule imaging

Abstract: The generation of high-density lipoprotein (HDL), one of the most critical events for preventing atherosclerosis, is mediated by ATPbinding cassette protein A1 (ABCA1). ABCA1 is known to transfer cellular cholesterol and phospholipids to apolipoprotein A-I (apoA-I) for generating discoidal HDL (dHDL) particles, composed of 100-200 lipid molecules surrounded by two apoA-I molecules; however, the regulatory mechanisms are still poorly understood. Here we observed ABCA1-GFP and apoA-I at the level of single molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(87 citation statements)
references
References 47 publications
9
75
3
Order By: Relevance
“…15,35 The direct interaction of apolipoproteins with ABCA1 is of key importance to ABCA1-mediated cholesterol efflux; however, the detailed molecular mechanisms are still elusive and several models have been proposed. 37,38 Using a novel single-molecule fluorescence tracking technique, Nagata et al 38 have shown that lipid efflux to apoA-I involves the ATPase-dependent conversion of mobile ABCA1 monomers into immobile homodimers in the plasma membrane: the model proposes that ABCA1 monomers translocate lipids at the plasma membrane and form dimers; only the dimers can bind apoA-I, with one molecule of apoA-I binding to each ABCA1 molecule in the dimer. ApoA-I is subsequently lipidated, and a discoidal HDL particle containing 2 apoA-I molecules is formed.…”
Section: Mechanisms and Roles Of Abca1-and Abcg1-mediated Cholesterolmentioning
confidence: 99%
“…15,35 The direct interaction of apolipoproteins with ABCA1 is of key importance to ABCA1-mediated cholesterol efflux; however, the detailed molecular mechanisms are still elusive and several models have been proposed. 37,38 Using a novel single-molecule fluorescence tracking technique, Nagata et al 38 have shown that lipid efflux to apoA-I involves the ATPase-dependent conversion of mobile ABCA1 monomers into immobile homodimers in the plasma membrane: the model proposes that ABCA1 monomers translocate lipids at the plasma membrane and form dimers; only the dimers can bind apoA-I, with one molecule of apoA-I binding to each ABCA1 molecule in the dimer. ApoA-I is subsequently lipidated, and a discoidal HDL particle containing 2 apoA-I molecules is formed.…”
Section: Mechanisms and Roles Of Abca1-and Abcg1-mediated Cholesterolmentioning
confidence: 99%
“…3 ) Real-time tracking of single ABCA1 molecules showed that ABCA1 forms immobile homodimers in the absence of apoA-I. Upon apoA-I addition, ABCA1 rapidly became mobile ( 61 ). A GPI-anchored protein, a typical raft-associated molecule, also forms homodimers and becomes immobile, which results in the formation of homodimer rafts in a cholesterol-dependent manner ( 62 ).…”
Section: Downloaded Frommentioning
confidence: 99%
“…8 Additional lipidation of apoA-I takes place in the golgi and at the plasma membrane in processes that are dependent on a dimeric form of ABCA1. 11,12 ApoA-I is also secreted from the liver into the extracellular space in a lipid-free or lipid-poor form. After secretion from the liver, the C-terminal domain of lipid-free apoA-I interacts with an extracellular loop of ABCA1 in a process that initiates the biogenesis of discoidal HDLs ( Figure 1B).…”
Section: Regulation Of Discoidal Hdl Biogenesis By Apolipoproteinsmentioning
confidence: 99%